Peningkatan Kapasitas dan Kualitas Produksi Usaha Roti Ikan: Strategi Berkelanjutan dalam Green Economy - Mohammad Wasil; Yunus Yunus; Lucky Rachmawati (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
The community service program conducted at the "Bu Sila" Fish Bread SME aims to enhance the capacity and quality of fish bread production by implementing sustainable strategies within the framework of the green economy. This program was carried out over six months, from July 28 to October 20, 2024. The main focus of the program was to provide appropriate technology support, including a hygienic oven machine, fish bread molds, and corrosion-resistant worktables. The provided technology was designed to improve production efficiency, maintain product quality, and support environmental sustainability by reducing waste and energy consumption. With the assistance of a baking oven and stainless steel or corrosion-resistant composite molds, the business partner was able to increase production capacity by 30–50%. This program not only enhances the partner's market competitiveness but also promotes a transition toward more environmentally friendly business practices. This aligns with the principles of the green economy, emphasizing resource efficiency and reducing negative environmental impacts. Overall, the program offers a long-term solution to improve productivity, quality, and business sustainability while strengthening the market competitiveness of fish bread products in an increasingly competitive market.